2015
DOI: 10.1007/s11284-015-1249-3
|View full text |Cite
|
Sign up to set email alerts
|

Capitulum and rosette leaf avoidance from grazing by large herbivores in Taraxacum

Abstract: Plants defense against herbivore damage is achieved through resistance and tolerance, of which resistance is composed of avoidance and antibiosis. Plants have developed various adaptations that facilitate escape from herbivory. We hypothesized that post-anthesis prostrate scapes in Taraxacum is an adaptation for avoidance of capitulum grazing by large herbivores. To test this hypothesis, we divided flowering into the following four stages based on the external appearance of the capitulum: green bud, yellow cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The phenotypic characteristic maintained in vegetative propagation might be the grazing avoidance mechanism that forms part of adaptation to grazing [ 69 ]. Although in this study we observed that the dwarf memory of L .…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic characteristic maintained in vegetative propagation might be the grazing avoidance mechanism that forms part of adaptation to grazing [ 69 ]. Although in this study we observed that the dwarf memory of L .…”
Section: Discussionmentioning
confidence: 99%
“…In rosette plants, such as Arabidopsis, the newly formed leaves give rise to a basal rosette: a whorl of leaves that has little to no elongation between successive nodes. The rosette habit is widespread amongst flowering plants and provides several advantages compared to taller, less compact plants, such as protection from (a)biotic stresses (Schaffer and Schaffer, 1979; Bello et al, 2005; Larcher et al, 2010; Thomson et al, 2011; Fujita and Koda, 2015). In Arabidopsis, light requirement for SAM activation can be overcome by availability of metabolizable sugars, such as sucrose, to the meristem (Roldán et al, 1999; Li et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, only the inflorescence was damaged, which may explain why the direct negative effect on the population growth rate of P. farinosa was not even stronger than that observed. Like other rosette-forming and prostrate herbs, P. farinosa avoids damage by ungulate grazers to vegetative parts better than do herbs with an upright growth form (Díaz et al 2001; Fujita & Koda 2015).…”
Section: Discussionmentioning
confidence: 99%